Reproductive biology of the Golden grey mullet Liza aurata, in the Gulf of Gabes (central Mediterranean, Tunisia) in the Gulf of Gabes (central Mediterranean, Tunisia) - ABDALLAH, C.; GHORBEL, M.; JARBOUI, O. (Mediterranean Marine Science, 2013)
In spite of its high commercial value, very few information are available on the biological feature of the Golden grey mullet in Tunisian waters (central Mediterranean). These data would be of great help in identifying the current stock state. In this study, Gonado Somatic Index (GSI), Hepato Somatic Index (HSI), condition factor (K), Length at first sexual maturity TL50 was calculated and the fecundity was estimated using the volumetric method. The Gonado Somatic Index (GSI) indicated that the spawning season of the Golden grey mullet extends from October to December. The monthly variation of Hepato-Somatic Index (HSI) indicates that L. aurata saves lipid reserves in liver. The species is sexually mature at 23.73, 23.84 and 23.79 cm TL respectively for female, male and combined sexes. In the present study the sex-ratio was unbalanced, with females dominating among large size individuals (TL > 24 cm). Absolute fecundity with a mean value of 286564 varied from a minimum of 210400 eggs for age 4 and a maximum of 533600 for age 7+.